KUALITAS PELAYANAN PENGADUAN MASYARAKAT DI PERUSAHAAN LISTRIK NEGARA DI AREA MANADO (STUDI KASUS PEMADAMAN LISTRIK) - Mandang, Olivia; Posumah, Johnny Hanny; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : This study aims to describe the quality of service of public complaints in the State electricalCompany in the area of Manado in a bid the development science of public administration. The complaintsservice funded by the State power company based on the provisions of article 29 of Act No. 30 of 2009 aboutelectric power, was founded to help the problems in terms of electricity. In this study uses the dimensions ofservice quality measurement kotler, where the quality of service in public complaints in the State electricalcompany in Manado area about power outages related to aspects of the Tangibles, Reliability, Responsiveness,Assurance, and can be said to have not been fullest emphaty. It is proven by the provision of the facilities, suchas the location of the parking of vehicles is not adequate, the community's lack of seating room, pitted a smallcustomer service, lack of employees down kelokasi, the lack of information of a power to the people and thelack of responsibility of the PLN. Research method used is descriptive qualitative research method throughinterviewing to 9 informant, observations directly, and search documents related to quality of service , even inthis research aided by the existence of guidelines for interviewing, recording device, and stationery to write.The results of the peneleitian in General makes it clear that the quality of service public complaints in the Stateelectrical company in manado area about a power outage has not been run with the maximum.Keywords: Quality Of Service, PLN Area Manado.Keywords: quality of service, PLN Area Manado)